2011
DOI: 10.1177/1074248410395019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes Using Intra-Aortic Balloon Pump in High-Risk Acute Myocardial Infarction With or Without Cardiogenic Shock

Abstract: The present meta-analysis suggests that patients with high-risk AMI without cardiogenic shock do not seem to benefit from the use of IABP as measured by in-hospital mortality, rate of reinfarction, and recurrent angina. However, in patients with AMI with cardiogenic shock (systolic blood pressure [SBP] < 90), there was significant reduction in mortality using IABP. The use of IABP is associated with increase in the rate of both moderate and severe bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 48 publications
3
41
0
4
Order By: Relevance
“…A meta-analysis of IABP use in patients with AMI showed no effect on outcome; however, in the subset of AMI and CS, there was significantly decreased in-hospital mortality with IABP compared with no IABP. 34 The Cochrane analysis conducted in 2010 generated similar results-the efficacy and safety of IABP versus standard therapy or LV assist device in AMI complicated by CS was examined-no evidence for survival benefit was seen with IABP with heterogeneous effects on hemodynamics and device-related complications (Figure 3). 35 The IABP-SHOCK Trial was a prospective randomized control trial evaluating clinical outcome in 45 patients with post-MI CS treated with primary PCI with or without IABP support.…”
Section: Post-mi and Cardiogenic Shockmentioning
confidence: 62%
See 1 more Smart Citation
“…A meta-analysis of IABP use in patients with AMI showed no effect on outcome; however, in the subset of AMI and CS, there was significantly decreased in-hospital mortality with IABP compared with no IABP. 34 The Cochrane analysis conducted in 2010 generated similar results-the efficacy and safety of IABP versus standard therapy or LV assist device in AMI complicated by CS was examined-no evidence for survival benefit was seen with IABP with heterogeneous effects on hemodynamics and device-related complications (Figure 3). 35 The IABP-SHOCK Trial was a prospective randomized control trial evaluating clinical outcome in 45 patients with post-MI CS treated with primary PCI with or without IABP support.…”
Section: Post-mi and Cardiogenic Shockmentioning
confidence: 62%
“…27,34 In summary, these data do not support routine use of IABP in AMI outside the setting of CS. However, it may be of benefit if there is evidence of impending hemodynamic instability.…”
Section: Circ Cardiovasc Intervmentioning
confidence: 77%
“…In contrast, Bahekar et al [12] analysed 6 cohorts containing 24,541 patients with IABP and reported a 28 % (p<0.0004) reduction in mortality in those receiving IABP.…”
Section: Ami With Csmentioning
confidence: 81%
“…A centrifugal pump then moves the blood over a membrane oxygenator before injecting it back into the common iliac artery The divergent observations from these large meta-analyses require some explanation. In the meta-analysis by Bahekar et al [12], there was no separation of those receiving thrombolysis and those treated by PCI. The apparent reduction in mortality in patients receiving thrombolysis may be explained by confounding influences and selection bias; patients receiving thrombolysis were younger, more often male and sicker patients deemed 'too ill' may have been excluded.…”
Section: Ami With Csmentioning
confidence: 97%
“…Peak diastolic pressure is increased and the end-systolic pressure is decreased during continuous inflation-deflation cycles, which results in a reduction of afterload and improved coronary flow. Previously reported as a first line strategy (class I C) [30] with scientific support from the SHOCK Trial Registry [31] and the National Registry of Myocardial Infarction-2 (NRMI-2) [32], IABP lost its position in guidelines due to several meta-analyses [33,34] and IABP-SHOCK II Trial [35] results with no further support of any IABP benefit. Unfortunately, while IABP is not efficient to ensure long-term survival, there is no well defined reason why the improvement in the haemodynamic status after IABP insertion is not a suitable predictor of better survival.…”
Section: Intra-aortic Balloon Pumpmentioning
confidence: 99%